THE IMPACTS OF INSTITUTIONAL HETERONORMY ON THE MENTAL HEALTH OF THE LGBTQIA+ POPULATION - Serrão Pimenta, Alessandra; Wilson Ramos da Conceição, Pedro (Revista Gênero e Interdisciplinaridade, 2021)
Sexual diversity has long been defined as a pathology, and although it is no longer considered a disease, prejudice and stigmatization remain present, generating social, psychological and physical consequences. Society is guided by standards that define heteronormativity as "normal" and homosexuality as "abnormal", although this thought is refuted by the scientific community, it still has a strong expression in society, promoting segregation and violence against LGBTQIA+. This article aims to analyze the impacts of institutional heteronormativity, predominant in society, and its implications in the process of mental health vulnerability in the LGBTQIA+ population. The article is a bibliographical research, with a qualitative and integrative approach, enabling the deepening of the theme and the understanding of fundamental concepts for the development of the study. The analyzed articles were selected and included in the research, as they are original articles, simple and systematic literature reviews. According to theoretical positions, health programs have a great deficit related to the humanization of the LGBTQIA+ community. The heteronormative patterns, perpetuated in society, imply the emergence of discriminatory attitudes, thus, it is necessary the apparatus of effective public policies that can guarantee the health of these individuals, in this sense, there is a need to confront the heteronormative pattern present in health services . The issues addressed here are intended to encourage more research that encourages inclusion and the formation of effective policies that bring the LGBTQIA+ community closer to quality public health.